THE INSTRUMENT USED IN MEASURING EMPLOYEE PRODUCTIVITY BASED ON SOCIAL MEDIA USAGE: A REVIEW - Mohamed, Shahrulanuar; Sidek, Safiah; Kudus, Norliah; Abu Hassan, Mahadi; Izharrudin, Siti Zakiah (Journal of Human Capital Development (JHCD), 2017)
Social media has become a necessity among organization in order to enhance the productivity or job performance among employees. It has been claimed as the effective communication channel among employee to corporate toward collaboration, knowledge sharing, etc. Nevertheless, as the social media become the most priority among individual and organization, it has also become one of the factors that contribute to the disruption of work productivity. Thus, this review paper aimed to conduct comparison analysis in the methodology used and the instrument adopted or developed by researchers in measuring the social media usage and employee productivity. There are 32 studies being selected and the majority of the study has been conducting quantitative approaches through an online survey in identifying the frequency of social media usage. From 32 studies only 5 studies have been applicable in measuring work productivity based on the impact of social media usage. The findings presented in this review paper will provide a deep understanding in designing new instrument in measuring the productivity of employee based on the social media usage rather than any negative factors that contribute to the lowest productivity at workplaces. Keywords: comparison analysis, social media usage, instrument, employee productivity